THEORETICAL FUNDAMENTALS OF DETERMINATION OF PROCESSES OF SEARCH, SELECTION AND SELECTION OF ENTERPRISE OF THE ENTERPRISE - VEDERNIKOV, M.; VOLYANSKA-SAVCHUK, L.; GLUSHKO, T.; ZELENA, M.; DANILKOVA, A. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article highlights the essential principles of search, selection, selection and selection of personnel as mechanisms for the formation and development of personnel policy in any enterprise. It is considered that the relevance of search, selection and recruitment has become one of the most important factors. It is substantiated that the search and selection of personnel is a continuation of the personnel policy implemented by the enterprise and one of the key elements of the personnel management system. The term of selection and recruitment, methods and directions of improvement are considered. The paper considers the issue of improving the recruitment and selection of personnel using modern HR-technologies. The principles of determining the processes of professional search, selection, selection of personnel, review of the history of the study of this issue, a brief description of the main tools of personnel selection. The complexity of personnel selection lies primarily in the need to systematize the actions of the personnel and management in organizing this process. The creation of a certain algorithm of actions in the selection and recruitment of personnel makes it possible to effectively carry out this process. That is why the issues of forming a system for the selection and recruitment of personnel are relevant, which makes it possible to reduce the cost of these activities and reduce staff turnover. There are two possible sources of attracting potential candidates: external and internal, depending on what type of personnel policy (open or closed) is adopted in this organization. Internal sources for filling vacant positions - internal competition, combination of professions, staff rotation. For all methods of personnel diagnostics, three criteria can be applied, such as the validity (theoretical and practical) of preventing the risk of discrimination and pre-emption; economic justification of the method. The above methods for evaluating candidates during selection can provide management with broad information about the capabilities of a particular employee, but they cannot answer the important question of whether a person will fully realize his knowledge and capabilities.